Heavy, unhealthy, and dangerous work as defined in Costa Rican labor legislation: an analysis of the obstacles to its proper implementation - Fernánadez Ávila, Karla (2025)
In the field of human security, Costa Rican legislation establishes labor categories known as heavy, unhealthy, and dangerous work. However, there is a regulatory gap in its application, which creates uncertainty both for workers and employers, limiting its implementation. The obstacles generated by this regulatory gap will be identified, and possible practical solutions will be proposed.